WTAP mediates the anti-inflammatory effect of Astragalus mongholicus polysaccharide on THP-1 macrophages - Long, Haijiao; Lin, Haiyue; Zheng, Pan; Hou, Lianjie; Zhang, Ming; Lin, Shuyun; Yin, Kai; Zhao, Guojun (Frontiers in Pharmacology, 2022)
Background: Astragalus mongholicus polysaccharides (APS) have anti-inflammatory, antioxidant and immunomodulatory effects. Recent studies have demonstrated the epigenetic regulation of N6-methyladenosine (m6A) in the development of inflammation. However, the effect of APS on m6A modification is unclear. Here, for the first time, we investigate the mechanism of m6A modification in APS regulation of THP-1 macrophage inflammation. Methods: We treated LPS-induced THP-1 macrophages with APS at different concentrations and times，and detected IL-6 mRNA and protein levels by quantitative real-time PCR (qRT-PCR) and western blot, respectively. The m6A modification level was detected by m6A quantification kit. The proteins that regulate m6A modification were screened by western blot. Wilms' tumor 1-associating protein (WTAP) was overexpressed in APS-treated THP-1 macrophages and the m6A modification level and IL-6 expressions were detected. Results: These findings confirmed that APS significantly abolished LPS-induced IL-6 levels in THP-1 macrophages. Meanwhile, APS reduced m6A modification levels and WTAP gene expression in THP-1 macrophages. Further overexpression of WTAP can significantly reverse APS-induced m6A modification level and IL-6 expression. Mechanistically, APS regulates IL-6 expression through WTAP-mediated p65 nuclear translocation. Conclusions: Overall, our study suggested that WTAP mediates the anti-inflammatory effect of APS by regulating m6A modification levels in THP-1 macrophages. This study reveals a new dimension of APS regulation of inflammation at the epigenetic level.